Heat field of the north-west part of the Dnieper basin of the Dnieper-Donets depression - Gordienko, V.V.; Gordienko, I.V.; Zavgorodnjaja, O.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The values of the deep heat flow were studied in 135 boreholes. The positive anomalies were detected. The anomalies have correlation with a fault zones in the crystalline foundation in south-west part regions. Single anomalous values occur in the north-east, but they are not combined into regional anomalies. A comparison of the results of geothermal studies with different physical fields was performed. The positive anomalies possibly correspond to the recent activation of this region.